Blood ethanol concentrations in patients attending special clinics in Glasgow. Issue 5 (October 1975) - Schofield, C B; Wilson, E; Patel, A R; McGhie, T; Wilson, G M
Abstract : Blood samples for measurement of ethanol concentration were taken on a routine basis from 543 male and 158 female patients attending Special Clinics in Glasgow. Ethanol was detected in 56 (10-3 per cent.) of the men and eight (5-1 per cent.) of the women, and at concentrations in excess of 0-1 g./l. in 37 (6-8 per cent.) and three (1-9 per cent.) respectively. In nine men and one woman, the blood ethanol concentration was over 0-8 g./l. when they attended the clinic. The majority (84 per cent.) of positive findings were obtained in specimens collected after 2 p.m. and one-quarter on Tuesday afternoons, the local half-day. The other peak periods related to attendance at football matches on Wednesday evenings, and to receiving wages on Friday mornings. Male new patients attending a clinic for the first time had the highest incidence, 32 (11-6 per cent.) having detectable amounts of ethanol among whom 26 (9-4 per cent.) had levels in excess of 0-1 g./l., compared with only 4-1 per cent. among those either returning to the clinics with a fresh infection or on surveillance. Only 5 per cent. of female patients attending for the first time and 3 per cent. of those on surveillance had detectable amounts of ethanol in the blood, compared with 9 per cent. of those few returning with fresh infections. Levels in excess of 0-1 g./1. were only found in promiscuous women. Those with concentrations in excess of 0-8 g./1. were unreliable attenders. Only one, a known alcoholic, completed surveillance; one defaulted after his fourth visit, four after the second, and four after the first visit.